Pengaruh Pengetahuan Perpajakan, Kesadaran dan Pengetahuan Tax Amnesty Pada Kepatuhan WPOP di KPP Pratama Gianyar - Kesumasari, Ni Kadek Intania; Suardana, Ketut Alit (E-Jurnal Akuntansi, 2018)
This study aims to determine the effect of knowledge taxation, awareness, and knowledge of tax amnesty on the compliance of individual taxpayers. This research was conducted at Tax Office (KPP) Pratama Gianyar. This study uses Slovin formula to determine the number of samples as many as 100 individual taxpayers registered in KPP Pratama Gianyar, by accidental sampling method. The data were collected through questionnaires. The analysis technique used is multiple linear regression. The results showed that knowledge of taxation, awareness, and knowledge of tax amnesty have a positive effect on the taxpayer compliance of individuals. Knowledge of taxation, awareness, and knowledge of tax amnesty affect personal taxpayer compliance of 77.1%, while the remaining 22.9% is influenced by other variables not included in the research model. Keyword : Taxation, awareness, knowledge of tax amnesty and compulsory obedience.